Inclusion Body Myositis: Laser Microdissection Reveals Differential Up-Regulation of IFN-γ Signaling Cascade in Attacked versus Nonattacked Myofibers - Ivanidze, Jana (American Society for Investigative Pathology, 2011)
Sporadic inclusion body myositis (IBM) is a muscle disease with two separate pathogenic components, degeneration and inflammation. Typically, nonnecrotic myofibers are focally surrounded and invaded by CD8(+) T cells and macrophages. Both attacked and nonattacked myofibers express high levels of human leukocyte antigen class I (HLA-I) molecules, a prerequisite for antigen presentation to CD8(+) T cells. However, only a subgroup of HLA-I(+) myofibers is attacked by immune cells. By using IHC, we classified myofibers from five patients with sporadic IBM as attacked (A(IBM)) or nonattacked (N(IBM)) and isolated the intracellular contents of myofibers separately by laser microdissection. For comparison, we isolated myofibers from control persons (H(CTRL)). The samples were analyzed by microarray hybridization and quantitative PCR. HLA-I up-regulation was observed in A(IBM) and N(IBM), whereas H(CTRL) were negative for HLA-I. In contrast, the inducible chain of the interferon (IFN) γ receptor (IFNGR2) and several IFN-γ–induced genes were up-regulated in A(IBM) compared with N(IBM) and H(CTRL) fibers. Confocal microscopy confirmed segmental IFNGR2 up-regulation on the membranes of A(IBM), which positively correlated with the number of adjacent CD8(+) T cells. Thus, the differential up-regulation of the IFN-γ signaling cascade observed in the attacked fibers is related to local inflammation, whereas the ubiquitous HLA-I expression on IBM muscle fibers does not require IFNGR expression.